Accessibility Impact to Government Programs on the Household Income Contribution at the Various Livelihood Sources of Farmers - M. Edi Armanto; Elisa Wildayana (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
This paper aimed (1) to describe the accessibility of farmers to programs made by the government for rural development, and (2) to analyze the impact of this accessibility on the contribution generating household income of farmers in South Sumatra wetlands. This research was an experimental research using Split Plot Design. The study resulted that accessibility had a significant effect on the income structure of farmers' households. If accessibility was high to very high, the sector and types of off-farm activities were more developed and diverse. Household income in low accessibility was dominated by subsistence agriculture, although the types of off-farm activities varied, but their contribution to total household income was very small. In high accessibility areas, the income contribution from subsistence farming was relatively small, but the diversity of activities was large, which could increase the total household income, i.e. trade, non-agricultural labor, forest income, government projects, beca, drivers, carpenters, welding, shipping, etc. The total income of households in high accessibility was higher than in low accessibility areas. The better the accessibility, the better the total household income will be as long as the government manages farmers in off-farm activities.